The Return to Family Intervention in Youth Services: A Juvenile Justice Case Study - Bazemore, Gordon (1995)
After more than a decade of relative neglect, youth services policymakers in the late 1980s began targeting the family as a primary focus of intervention in the response to a range of deviant behavior. One recent example of this return to family intervention has been a renewed emphasis on family services in juvenile courts and juvenile justice agencies. This case study describes one attempt to implement a new family-focused intervention approach as part of a larger return to treatment-oriented probation services in an urban juvenile justice system. Based on interviews and participant observation data gathered during a nine month field study in a Florida county, this paper describes ideological resistance, role conflict, and the informal adaptations of delinquency case managers in response to the new demands of this agenda. Implications for implementation of such policies in juvenile justice and other social service organizations, as well as conceptual questions about the logic and efficacy of the family focus policy itself, are discussed